Double-layered health benefits: green space as a Third Place for everyday active mobility trips - Liu, Yu; Maurer, Megan Lynn; Skov-Petersen, Hans; Tollin, Nicola; Olafsson, Anton Stahl (Frontiers in Sustainable Cities, 2023)
The present paper addresses the timely need, across research and practice, to ask: how do we plan sustainable and healthier cities in a synergetic way for everyday life? Currently, urban dwellers are facing significant health challenges, especially physical inactivity. There is increasing awareness of the need to initiate active living strategies for urban dwellers to confront this challenge. Active mobility—walking and cycling—is the core of active living strategies and is promoted as both a type of physical activity and a mode of transport. However, uptake of active mobility faces many barriers, including lack of motivation and longer travel times. This paper unfolds the potential of green spaces as Third Places that can potentially counteract the challenges and in return, deliver double-layered health benefits. The sensory experiences provided by urban green spaces and associated health benefits have been largely investigated; yet, little is focused on how these experiences can be integrated as a part of daily living activities. This paper gives voice to everyday practice and discusses how these experiences can be utilized as planned motivations for the use of active mobility. This paper aims to contribute to the knowledge for future research and practice, and bring forward an open debate about healthier cities, which can bridge all related professions across urban sectors.